2012
DOI: 10.1038/aja.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA targeting HMGN5 induces apoptosis via modulation of a mitochondrial pathway and Bcl-2 family proteins in prostate cancer cells

Abstract: We investigated the importance of HMGN5, a nuclear protein that binds to nucleosomes, unfolds chromatin, and affects transcription, in the LNCaP prostate cancer cell line. We also examined the molecular mechanisms that promote apoptosis of LNCaP cells after infection with small interfering RNA (siRNA) targeting HMGN5 (siRNA-HMGN5). The androgen-dependent LNCaP human prostate cancer cells were infected with siRNA-HMGN5. Apoptosis was detected using the Annexin V-PE/7-AAD double staining and the terminal deoxynu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Knockdown of NSBP1 causes cell cycle arrest and promotes cell apoptosis of prostate cancer cells possibly by inhibiting cyclin B1 and Bcl-2 expression levels (15). Similarly, Zhang et al showed that NSBP1 gene silencing results in increased mitochondria-mediated cell apoptosis in prostate cancer cells (22). Furthermore, NSBP1 is overexpressed in glioma clinical tissues, and knockdown of NSBP1 induces cell cycle arrest in the G1 phase, inhibits cell proliferation and promotes cell apoptosis in glioma cells in vitro (16).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of NSBP1 causes cell cycle arrest and promotes cell apoptosis of prostate cancer cells possibly by inhibiting cyclin B1 and Bcl-2 expression levels (15). Similarly, Zhang et al showed that NSBP1 gene silencing results in increased mitochondria-mediated cell apoptosis in prostate cancer cells (22). Furthermore, NSBP1 is overexpressed in glioma clinical tissues, and knockdown of NSBP1 induces cell cycle arrest in the G1 phase, inhibits cell proliferation and promotes cell apoptosis in glioma cells in vitro (16).…”
Section: Discussionmentioning
confidence: 99%
“…HMGN5 plays an important role during development and tumorigenesis (8,12,13), and HMGN5 expression is upregulated in prostate (14), bladder (15), clear cell renal cell carcinoma (16), breast (17), cutaneous squamous (18) and ovarian cancer (19), suggesting an association between high HMGN5 expression and tumorigenesis. In our previous studies, we found that HMGN5 was overexpressed in prostate cancer tissues and prostate cancer cell lines, and downregulation of HMGN5 with shRNA caused cell cycle arrest, growth inhibition and apoptosis in vitro and in vivo (20,21). We also found that gemcitabine downregulated the expression of HMGN5 (22).…”
Section: Introductionmentioning
confidence: 89%
“…In addition, HMGN5 expression is upregulated with the development of several cancers, including squamous cell carcinoma, breast and bladder cancer, renal cell carcinoma, and gliomas (Gerlitz, 2010; Ji et al, 2012b; Li et al, 2006a; Qu et al, 2011; Tang et al, 2008b; Wahafu et al, 2011). Knockout of HMGN5 by RNAi inhibits cell proliferation and increases apoptosis in cancer cells (Chen et al, 2012b; Ji et al, 2012b; Zhang et al, 2012c). …”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%